Cloning and characterization of A cDNA encoding prohibitin1 from Lampetra japonica and its expression analysis - Li, T. S.; Chen, C.; Gao, Y.; Li, Q. W. (Cellular and Molecular Biology, 2012)
To investigate that prohibitin is probably concerned in B-lymphocyte-like cells mediated signal pathways in Lamprey, a necessary and fundamental plan is firstly conducted. A full-length cDNA encoding the prohibitin1 protein was cloned from Lampetra japonica by EST sequence analysis in L. japonica leukocyte cDNA library conducted by our laboratory. Prohibitin1 contains a 828bp open reading frame, encoded 275 amino acids residues, and molecular weight is 29.9517KD, isoelectric point is 6.93, consists of 31 negatively charged amino acids residues (Asp+Glu) and 21 positively charged ones (Arg+Lys). The Prohibitin1 gene sequence from L. japonica is 71% identical to the ones of other 24 eukaryotic species, which shows the putative prohibitin1 gene is highly conserved. Western blotting analysis results showed the recombinant proteins were the target proteins in prokaryote. Real-time quantitative polymerase chain reaction analysis indicated that the expression of the prohibitin1 gene is significantly up-regulated in leukocyte, heart and gill of L. japonica by LPS stress treatment. In conclusion, we have cloned and identified the full-length cDNA of Prohibitin1 in L. japonica and found that it was related to adaptive immune response in lamprey for the first time.